Analysis of the Rasch Model Data Needs for the Development of Blended Learning on Character Values and Learning Motivation - Eko Risdianto; Eko Sumartono (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This inquire is about the portion of the RD inquire about utilizing the ADDIE demonstrate. In any case, this investigate is as it were constrained to the examination organize, specifically analyzing the require for the improvement of mixed learning models in PAUD instruction to develop character values and understudy inspiration to memorize. The populace is all PAUD instructors in Rejang Lebong. The sample of the test  are 75 individuals with likelihood examining procedure. The survey was conducted on October 2021. The instrument utilized was a survey sheet that using a adjusted Likert scale. The survey tried utilizing the Rasch show with the assistance of the Winstep application. The results show that the quality of the questionnaire on the needs of PAUD teachers in Rejang Lebong for the blended learning model is very good. So that it can be used to determine the response to the development of blended learning models. From the results comes about of the examination of the respondents and the things of the survey, it appears that most of the respondents concur with all the supporting things, in this way showing that the reaction to the improvement of the blended learning model is in understanding